2005
DOI: 10.1038/sj.ejcn.1602172
|View full text |Cite
|
Sign up to set email alerts
|

Long-term maintenance of weight loss with sibutramine in a GP setting following a specialist guided very-low-calorie diet: a double-blind, placebo-controlled, parallel group study

Abstract: Objective: Very-low-calorie diets (VLCDs) are used to promote short-term weight loss in obese patients. However, long-term maintenance of weight loss is generally poor. We assessed the efficacy and safety of sibutramine in maintaining weight loss achieved in obese patients by means of a 3-month VLCD. Design: A multicenter double-blind, parallel-group trial conducted over 18 months, following a 3-month open label VLCD runin. Setting: Eight hospital centers in The Netherlands, with subsequent follow-up in genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 18 publications
1
58
1
Order By: Relevance
“…47 Medically supervised programs (OPTIFAST, Health Management Resources) may induce losses of 15-25% of initial weight using meal replacements, [48][49][50][51][52] although patients have difficulty sustaining losses of this size, even when provided weight maintenance therapy. 48,51,53 Pharmacotherapy (e.g., orlistat, sibutramine), when prescribed alone, produces modest losses of 4 to 5% of initial weight. 54 However, interventions that combine pharmacotherapy with intensive lifestyle modification may induce losses of 8-12% of initial weight.…”
Section: Discussionmentioning
confidence: 99%
“…47 Medically supervised programs (OPTIFAST, Health Management Resources) may induce losses of 15-25% of initial weight using meal replacements, [48][49][50][51][52] although patients have difficulty sustaining losses of this size, even when provided weight maintenance therapy. 48,51,53 Pharmacotherapy (e.g., orlistat, sibutramine), when prescribed alone, produces modest losses of 4 to 5% of initial weight. 54 However, interventions that combine pharmacotherapy with intensive lifestyle modification may induce losses of 8-12% of initial weight.…”
Section: Discussionmentioning
confidence: 99%
“…Sibutramine, on the other hand, acts by inhibiting the reuptake of serotonin and noradrenalin in the central nervous system appetite center, thus increasing satiety [135]. Compared to placebo, sibutramine induces more pronounced body weight reduction of between 5% and 10% in obese patients [136][137][138][139]. As with other anti-obesity drugs, the combined effect of lifestyle modification and sibutramine treatment is more effective than with just sibutramine treatment [138,140].…”
Section: Weight-reducing Treatmentmentioning
confidence: 99%
“…However, long-term maintenance of weight loss is generally poor. Weight loss achieved after a 3-month VLCD is more effectively improved and maintained with sibutramine plus a diet and exercise programme than with placebo over a followup period of 12-18 months 12,13 (Table 1). These results agree with those obtained in the STORM study 2 , which demonstrated maintenance of weight reduction with sibutramine than with a conventional dietetic approach.…”
Section: Binge Eatingmentioning
confidence: 99%